Nostradamus for dummies - Ross, Scarlett (Wiley, 2005)
Michel Notredame, or Nostradamus (1503-1566), was a French physician, astrologer, and prophet whose books of visionary four-line verses have intrigued and beguiled readers for hundreds of years. Now, with this fun and easy guide, everyone can finally get a handle on Nostradamus and his "Centuries" of prophecies, which many people believe to have predicted the French Revolution, the rise of Hitler, the Kennedy assassination, and 9/11, among other events. The book covers Nostradamus's life and beliefs, his use of cryptic language and anagrams, interpretations of his work that link it to specific historical incidents, and critics who are skeptical of his prophecies. It also explores the implications of his work on the past, present, and future, and much more!